Echocardiography: A Case of Coronary Sinus Endocarditis. Issue 9 (28th June 2014) - Kwan, Clara; Chen, On; Radionova, Svetlana; Sadiq, Adnan; Moskovits, Manfred
Mini‐Abstract We present a case of a 23‐year‐old woman with end‐stage renal disease on hemodialysis (HD) via a permacath for the past year, who was found to have endocarditis of the coronary sinus (CS). While patients on HD have higher rates of infective endocarditis (IE), involvement of the CS is rare with only a few cases reported. In our case, the presence of a HD catheter may have predisposed her to IE of the CS. Furthermore, her blood cultures were positive for Acinetobacter baumannii which is a rare pathogen but can be found in hospital settings and in patients on HD.